2020
DOI: 10.1093/chromsci/bmaa091
|View full text |Cite
|
Sign up to set email alerts
|

Andrographolide: A Review of Analytical Methods

Abstract: Bicyclic diterpenoid lactone andrographolide is regarded as a “natural antibiotic” as it is known to exhibit a range of bioactivities including anti-inflammatory, antibacterial, antipyretic, antineoplastic, cardioprotective, hepatoprotective and hypoglycaemic, and is present in Andrographis paniculata. The aim of this article is to review the information on analytical methods for andrographolide in biological samples, pharmaceutical formulations and plant materials. This article includes various techniques suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 59 publications
1
22
0
Order By: Relevance
“…ex Nees, can be used to treat cold, fever, sore throat, sore mouth and tongue (Jiang et al, 2013). In recent decades, with the increasing interest in the research of this phytomedicine, abundant of researches has proven that the intervention of modern novel technics to excavate the main effective components from it has become a hot spot (Patil & Jain, 2021; Stopponi et al, 2021). It has been reported that andrographolide (Figure 1), ((3E,4S)‐3‐[2‐[(1R,4aS,5R,6R,8aS)‐6‐hydroxy‐5‐(hydroxymethyl)‐5,8a‐dimethyl‐2‐methylidene‐3,4,4a,6,7,8‐hexahydro‐1H‐naphthalen‐1‐yl]ethylidene]‐4‐hydroxyoxolan‐2‐one; PubChem CID: 5318517, CAS No.…”
Section: Introductionmentioning
confidence: 99%
“…ex Nees, can be used to treat cold, fever, sore throat, sore mouth and tongue (Jiang et al, 2013). In recent decades, with the increasing interest in the research of this phytomedicine, abundant of researches has proven that the intervention of modern novel technics to excavate the main effective components from it has become a hot spot (Patil & Jain, 2021; Stopponi et al, 2021). It has been reported that andrographolide (Figure 1), ((3E,4S)‐3‐[2‐[(1R,4aS,5R,6R,8aS)‐6‐hydroxy‐5‐(hydroxymethyl)‐5,8a‐dimethyl‐2‐methylidene‐3,4,4a,6,7,8‐hexahydro‐1H‐naphthalen‐1‐yl]ethylidene]‐4‐hydroxyoxolan‐2‐one; PubChem CID: 5318517, CAS No.…”
Section: Introductionmentioning
confidence: 99%
“…TM exerts its effect through different mechanisms compared to conventional antibiotics, which might be of clinical value in the treatment of infectious diseases associated with biofilms ( Ordonez et al, 2011 ; Borges et al, 2015 ). Andrographis paniculata , a highly abundant natural product and medicinal plant, is regarded as a “natural antibiotic” ( Patil and Jain, 2020 ). Pharmacological studies have shown that it possesses anti-inflammatory, antibacterial, and antipyretic properties ( Patil and Jain, 2020 ) and it has been used to treat a variety of infectious diseases, such as furuncle, upper respiratory tract infection, and chronic pharyngitis caused by MRSA infection.…”
Section: Introductionmentioning
confidence: 99%
“…Andrographis paniculata , a highly abundant natural product and medicinal plant, is regarded as a “natural antibiotic” ( Patil and Jain, 2020 ). Pharmacological studies have shown that it possesses anti-inflammatory, antibacterial, and antipyretic properties ( Patil and Jain, 2020 ) and it has been used to treat a variety of infectious diseases, such as furuncle, upper respiratory tract infection, and chronic pharyngitis caused by MRSA infection. The antibacterial activity is primarily attributed to andrographolide (AG), the active constituent of the herb ( Liew et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the technique requires the compounds’ derivatization and their metabolites (Robards et al 1999 ). Moreover, the detection limit is influenced by the choice of detector employed (Patil and Jain 2021 ). In recent times, common detectors used to analyse target compounds include chemical ionization, flame ionization detector, electron impact, tandem mass spectrometry, and single quadrupole (Petrović and Barceló 2000 ; Clara et al 2007 ).…”
Section: Analysis Of Surfactantsmentioning
confidence: 99%